Early detection of doxorubicin-induced cardiotoxicity and its prevention by carvedilol - Ajmal, Khalida; Sharif, Mahjabeen; Afzal, Ayesha; Khan, Bushra Tayyaba; Ajmal, Muhammad (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective was to detect doxorubicin (Dox) - induced myocardial injury at early stage by quantitative estimation of cardio specific protein, cardiac troponin I (cTnI) and to explore the cardioprotective effects of carvedilol. Methods: The study design was lab-based randomized controlled in-vivo in rabbits conducted from January to August 2012. Cardiotoxicity was produced by single intravenous injection of 12 mg/kg body weight (BW) of Dox in a group of rabbits, control group was treated with normal saline only and the rabbits of third group were pre-treated with carvedilol 30 mg/kg of BW for 10 days before injecting Dox. Results: Dox induced cardiotoxicity was depicted by markedly raised serum levels of cTnI, creatine kinase-MB, lactate dehydrogenase, and Grade 3 necrosis of the heart tissue in rabbits. The pre-treatment with carvedilol resulted in improved serum levels of these biomarkers and the histological picture of heart tissue. Conclusions: Quantitative serum estimation of cTnI detects the presence of cardiotoxicity much before cardiac dysfunctions can be revealed by any other diagnostic technique. It can lead to significant economic impact in the management of cancer patients because the troponin-negative subjects can be excluded from long-term cardiac monitoring programs that involve high costs imaging techniques. The outcome of Dox chemotherapy can be made successful with the concurrent use of carvedilol.